The Implication of Digital Marketing that Influence the Political Decision to Vote - Yanto Ramli; Erna Sofriana Imaningsih; Aldina Shiratina; Mochamad Soelton (Yayasan Ilomata, 2021)
The intention of this research is to understand how did the winner of the election win the heart of the prospective voters and which of the variables that has the highest influence on the decision to vote for the candidate, the respective variables are: positioning and social media marketing towards the decision to vote in relating to the political marketing as the intervening variable. The data was collected from the distribution of questionnaire, the population are the voters of the election in West Java, Indonesia. This research is using Purposive Sampling as the data processing and the analysis tool is using Partial Least Square. The results indicate that both positioning and social media marketing have positive and significant effect towards political marketing, and the variable of positioning have the most significant influence towards decision to vote compare to social media marketing. The results show that the positioning of a candidate is very important to engage the decision of the voters to vote for them. Eventhough the social media marketing is also playing an important part to engage their voters.